Facile synthesis of highly-dispersed Pt/CeO2 by a spontaneous surface redox chemical reaction for CO oxidation. Issue 13 (21st June 2018) - Cao, Fangxian; Zhang, Sai; Gao, Wei; Cao, Tian; Qu, Yongquan
Abstract : A highly-dispersed Pt/CeO2 catalyst synthesized through a spontaneous surface redox reaction between metal ions and Ce(OH)3 /CeO2 nanorods delivers high CO oxidation activity. Abstract : A spontaneous surface redox chemical reaction between the Ce(OH)3 /CeO2 nanorod precursor and metal salt was developed to synthesize a highly dispersed Pt nanocatalyst anchored on porous CeO2 nanorods. The strong electronic metal–support interaction enables the high catalytic activity of the as-synthesized catalyst for CO oxidation.